2012
DOI: 10.1590/s0103-51502012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Análise postural da coluna vertebral: estudo comparativo entre surdos e ouvintes em idade escolar

Abstract: INTRODUÇÃO: A postura é determinada pela atuação dos sistemas visual, somatossensorial e vestibular, situado na orelha interna. Crianças com perda auditiva sensório-neural podem apresentar problemas na regulação do controle postural, favorecendo o surgimento de desvios e alterações posturais na coluna vertebral, provocados, possivelmente, pela hipoatividade do sistema vestibular, em decorrência da lesão na orelha interna. OBJETIVOS: Identificar e comparar a distribuição de alterações posturais na coluna verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
1
0
Order By: Relevance
“… 13 14 15 16 In this context, Melo et al, who evaluated the spinal posture of 88 students (44 deaf and 44 normally hearing students, aged 7 to 17 years), reported that the deaf students showed significantly more postural changes in the spine when compared with normally hearing students, as observed in this study. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 13 14 15 16 In this context, Melo et al, who evaluated the spinal posture of 88 students (44 deaf and 44 normally hearing students, aged 7 to 17 years), reported that the deaf students showed significantly more postural changes in the spine when compared with normally hearing students, as observed in this study. 17 …”
Section: Discussionmentioning
confidence: 99%